How Good Are Machine Learning Clouds for Binary Classification with Good Features? - Zhang, Hantian; Zeng, Luyuan; Wu, Wentao; Zhang, Ce (Proceedings of the 2017 Symposium on Cloud Computing (SoCC 2017), 2017)
In spite of the recent advancement of machine learning research, modern machine learning systems are still far from easy to use, at least from the perspective of business users or even scientists without a computer science background. Recently, there is a trend toward pushing machine learning onto the cloud as a "service," a.k.a. machine learning clouds. By putting a set of machine learning primitives on the cloud, these services significantly raise the level of abstraction for machine learning. For example, with Amazon Machine Learning, users only need to upload the dataset and specify the type of task (classification or regression). The cloud will then train machine learning models without any user intervention.